Analisis Uraian Tugas Tenaga Administrasi Sekolah Bidang Kepegawaian SLTA di Pulau Sipora Kabupaten Kepulauan Mentawai - Yosi Angel Dirawati; Rusdinal Rusdinal; Nelitawati Nelitawati; Yulianto Santoso (CV. ITTC INDONESIA, 2026)
This descriptive qualitative multi-site study evaluates the operational alignment of formal job descriptions for school administrative staff (TAS) in personnel affairs across senior high schools (SLTA) on Sipora Island, a remote area in Mentawai Islands. Data were gathered from four schools (SMA Swasta Penabur Berkat, SMAN 2 Sipora, SMKN 1 Kepulauan Mentawai, and SMAN 1 Sipora) through interviews, observations, and document audits involving eight key informants. Framed within the POAC (Planning, Organizing, Actuating, Controlling) management framework, the study reveals a persistent implementation gap. Daily workflows show only a 70% to 80% adherence rate to formal job descriptions, heavily dominated by reactive, situational vertical mandates (management by crisis). Five critical structural barriers sustain this gap: severe misalignment in educational backgrounds (mismatch), lack of localized continuous training, acute infrastructural deprivations (frequent power outages and unstable satellite internet connection), absence of written Standard Operating Procedures (SOPs), and operational overload due to extreme staff multi-tasking. This study recommends human resource recalibration, the development of contextual SOPs, and inclusive digital administration training for schools in isolated archipelagic networks.